2017
DOI: 10.1186/s12871-017-0365-8
|View full text |Cite
|
Sign up to set email alerts
|

Does an electronic cognitive aid have an effect on the management of severe gynaecological TURP syndrome? A prospective, randomised simulation study

Abstract: BackgroundLack of familiarity with the content of current guidelines is a major factor associated with non-compliance by clinicians. It is conceivable that cognitive aids with regularly updated medical content can guide clinicians’ task performance by evidence-based practices, even if they are unfamiliar with the actual guideline. Acute hyponatraemia as a consequence of TURP syndrome is a rare intraoperative event, and current practice guidelines have changed from slow correction to rapid correction of serum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In all, 13 randomised controlled trials were included and their findings were reported in 16 publications [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Details of the screening process are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all, 13 randomised controlled trials were included and their findings were reported in 16 publications [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Details of the screening process are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 . Two of the trials were assessed to be at overall low risk of bias [ 27 , 33 , 34 ], nine to have some concerns [ 22 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 31 , 32 , 35 ] and two were at high risk of bias [ 20 , 21 ]. In the 13 instances where clarification of trial methodology or missing data was needed, seven authors responded with the required information [ 22 , 25 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this technique is also associated with technical difficulties, takes longer to reach adequate levels of analgesia, can lead to blockade failure; patients can also experience post-dural puncture lumbago and back pain. [ 19 21 ] The existing literature predominantly suggests that sensory level should not be greater than T9 in order to observe patient symptoms for potential early TURP syndrome such as versical perforation. [ 22 , 23 ] However, some of the previous reports show that spinal anesthesia can significantly impair thermoregulation by altering afferent thermal inputs, inhibiting vasomotor and shivering responses, redistributing body heat, and predisposing patients to perioperative hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the evidence supporting the use of digital CAs instead of paper-based CAs is still inconclusive. In some simulation studies, digital CAs significantly improved decision-making and treatment, 9,10 whereas other studies did not observe any advantage when using a screenbased CA. 11 However, it appears that familiarization and training with the CA is of greater importance for successful implementation than the format (e.g., paper or electronic) itself.…”
Section: Background and Significancementioning
confidence: 94%